Syringic acid demonstrates better anti-apoptotic, anti-inflammatory and antioxidative effects than ascorbic acid via maintenance of the endogenous antioxidants and downregulation of pro-inflammatory and apoptotic markers in DMN-induced hepatotoxicity in rats - Olubisi E. Adeyi; Oluwatobi T. Somade; Babajide O. Ajayi; Adewale S. James; Akindele O. Adeyi; Zainab M. Olayemi; Nafisat B. Tella (Biochemistry and Biophysics Reports, 2023)
Dimethyl nitrosamine (DMN) is a known hepatotoxin, carcinogen, and mutagen. This study is therefore carried out to investigate the therapeutic effects of syringic acid (SYRA) and ascorbic acid (ASCA) in DMN-induced hepatic injury in rats. Following DMN administrations, malondialdehyde (MDA), nitric oxide (NO) and reduced glutathione (GSH) as well as activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), glutathione peroxidase (GPx), catalase (CAT), and superoxide dismutase (SOD) were significantly increased. Also significantly increased were levels of tumor necrosis factor-α (TNF-α), interleukin 1β (IL-1β), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). Following treatment with SYRA and ASCA, the activities of ALT, AST, GPx, CAT and SOD, as well as MDA, GSH, TNF-α, IL-1β, and NFkB levels were significantly reduced. Overall, both treatments were effective, but SYRA had a better therapeutic effect than ASCA. Therefore, this promising potential of SYRA can be taken advantage of in the treatment of DMN-induced hepatic injury.